2015
DOI: 10.1007/8904_2015_469
|View full text |Cite
|
Sign up to set email alerts
|

GM2-Gangliosidosis, AB Variant: Clinical, Ophthalmological, MRI, and Molecular Findings

Abstract: GM2-gangliosidosis, AB variant is a very rare form of GM2 gangliosidosis due to a deficiency of GM2 activator protein, associated with autosomal recessive mutations in GM2A. Less than ten patients, confirmed by molecular analysis, have been described in the literature.A 12-month-old Hmong girl presented to the neurometabolic clinic for evaluation of global developmental delay, hypotonia, and cherry red spots. The parents were not known to be consanguineous. Her examination was remarkable for hypotonia with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…6 Renaud et al showed delayed myelination and hyperintensity of the posterior thalami in the region of the pulvinar nuclei. 7 Similar changes have been reported for classical gangliosidosis, especially in the basal ganglia, but also in the thalamus [8][9][10] as well as periventricular white matter. 11,12 These signs were also seen in our patients, both of which showed signal changes in the basal ganglia and some myelination delay: one showed signal changes of periventricular white matter and the other some signal changes of the posterior thalami at 14 months.…”
Section: Discussionsupporting
confidence: 70%
“…6 Renaud et al showed delayed myelination and hyperintensity of the posterior thalami in the region of the pulvinar nuclei. 7 Similar changes have been reported for classical gangliosidosis, especially in the basal ganglia, but also in the thalamus [8][9][10] as well as periventricular white matter. 11,12 These signs were also seen in our patients, both of which showed signal changes in the basal ganglia and some myelination delay: one showed signal changes of periventricular white matter and the other some signal changes of the posterior thalami at 14 months.…”
Section: Discussionsupporting
confidence: 70%
“…It is an extremely rare disease and only 16 cases have been reported so far, of which 9 cases only are proven by molecular studies (Table 1). [3][4][5][6][7][8][9][10][11]…”
Section: Case Reportmentioning
confidence: 99%
“…Comparison of present case with previous proven cases. 3-11 Schroder et al,1991, Xie et al, 1992 Schroder et al, 1993 5 Schepers et al, 1996 6 Schepers et al, 1996 6 Chen et al, 1999 7 Kolodny et al, 2008 8 Renaud et al, 2015 9 Kustermann et al, 2015 10 Sheth et al…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…(10, 11) located in chromosome 5q31.3-q33.1 (12)(13)(14) The GM2 activator deficiency is caused by mutations in the GM2A gene encoding the GM2 activator protein. (15) Different mutations have been reported related to GM2A, (16)(17)(18)(19)(20)(21)(22) but interestingly, some study shows that, mutation in GM2A Leads to a Progressive Chorea-dementia Syndrome. (23) ELISA system can be used as diagnosis tool as well as therapeutic evaluation of GM2 gangliosidoses using anti-GM2 ganglioside antibodies (24) Can also be diagnosed by demonstrating accumulation of GM2 in the CSF of patients with normal hexosaminidase activity.…”
Section: Introductionmentioning
confidence: 99%